Quantifying Urban Sprawl for Rajkot City using Geospatial Technology (International Journal of Built Environment and Sustainability, 2016)
Urban sprawl is one of the avidly urban issues today. “Sprawling” means the spreading of urban area towards rural area surrounding it. There are different social and economic factors which led to urban sprawl. The study of urban sprawl in this paper attempts to measure the sprawl of urban areas into rural areas and the type of sprawl and the pre-dominant causes responsible for sprawl. It first reviews and analyses past research on the definitions of urban form, compactness and sprawl, and corresponding quantitative variables. Measures of urban sprawl will be identified and procedures will be developed to compute these indicators in GIS environment. The indicators of sprawl defined by (Galster et al, 2001) are considered as major characteristics of sprawl which have been adopted in this paper to develop a set of variables for quantification, characterization and dimension of sprawl.The study has been done on grid level (Grid Size = 500m x 500 m). The density index shows that in 2001 Rajkot had 9292 persons per grid of 500 meters x 500 meters which has decreased to 7394 persons per grid which shows that the population is moving from center to outer fringes. The value of concentration index has decreased from 0.56 in 2001 to 0.23 in 2011 which shows the sprawl development pattern. Centrality has been one of the major indicators of urban sprawl the value of centrality has been observed as 3.7 in 2001 and it has increased to 7.6 in 2011 which indicates sprawl.